2021
DOI: 10.3389/fcimb.2021.783085
|View full text |Cite
|
Sign up to set email alerts
|

GP IIb/IIIa-Mediated Platelet Activation and Its Modulation of the Immune Response of Monocytes Against Candida albicans

Abstract: Candida albicans is the most common fungal pathogen in humans, causing invasive disease and even potentially life-threatening systemic infections when tissue homeostasis is disrupted. Previous studies have identified an essential role of platelets in infection and immunity, especially when they are activated. However, it is still unclear whether platelets can be activated by C. albicans, and even less is known about the role of platelets in C. albicans infection. Herein, we showed that C. albicans induced plat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 47 publications
(86 reference statements)
0
5
0
Order By: Relevance
“…[29]. In contrast, it is better known that the α IIb β 3 integrin plays a central role in recognizing C. albicans [30]. In addition, Dectin-1 and CD206, identified on platelets in this study, could have a relevant role in binding C. albicans based on the background of these receptors [31,32].…”
Section: Discussionmentioning
confidence: 63%
“…[29]. In contrast, it is better known that the α IIb β 3 integrin plays a central role in recognizing C. albicans [30]. In addition, Dectin-1 and CD206, identified on platelets in this study, could have a relevant role in binding C. albicans based on the background of these receptors [31,32].…”
Section: Discussionmentioning
confidence: 63%
“…In another study, plasma L-arginine levels were shown to correlate inversely with the severity of COVID-19 [23]. This study also showed that the expression of the activated GP IIb/IIIa complex, known to be involved in platelet activation [23,24], is higher in patients with severe COVID-19 compared to healthy patients and inversely correlated with the plasma concentration of L-arginine [25].…”
Section: Introductionmentioning
confidence: 59%
“…Qualitative studies to date have examined wider patient experience. They revealed several common themes, including symptom variability, physical and intellectual fatigue, patients' burden of accessing care and fear of a permanent reduction in physical and cognitive abilities [16][17][18][19][20][21][22][23][24][25][26][27]. Cognitive complaints and persistent fatigue have been reported in the literature among the most debilitating symptoms for patients diagnosed with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyze the transcription of the efflux system genes MDR1, CDR1 , and CDR2, the PCR was performed using PCR amplifier "BioRad CFX96" (BioRad, Singapore) using Extra Mix for reverse transcription and quantitative real-time PCR in a one-step method (BioLabMix, Novosibirsk, Russia) with SYBR Blue under conditions recommended by the manufacturer. The oligonucleotides used for the qRT-PCR are shown in Table 1 [ 66 , 67 , 68 ]. A total RNA was extracted from planktonic C. albicans 688 cells subjected to 48-h treatment with either fluconazole or F131 .…”
Section: Methodsmentioning
confidence: 99%